Pelatihan UI/UX Menggunakan Figma Untuk Meningkatkan Kompetensi Di Bidang Desain Guru MGMP RPL SMK Provinsi Jawa Timur - Iqbal Ramadhani Mukhlis; Sinarring Azi Laga; Gaguk Suprianto; Deny Hermansyah; Mochamad Anang Karyawan; Heri Suprianto (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2023)
Teachers are professional educators who have the main task of educating and guiding students at school. A teacher must have 4 main competencies, namely pedagogic competence, personal competence, social competence and professional competence. One of the supporting professional needs to support the teaching and learning process is to attend workshops and training. Most of the MGMP RPL SMK teachers in East Java Province only focus on the field of Software Engineering so they forget about the field of user interface and user experience which are supporting components of an application. The MGMP RPL teachers' knowledge and skills in UI and UX design are still relatively low, so they need to be provided with UI/UX training in the form of mobile applications and website applications using figma. This training is held online with a duration of 2 days, 3 speakers every day. The output of this training is 55 user interface and user experience designs for mobile applications and website applications